Efficacy of oscillating - Rotating toothbrush (Oral -B) on periodontal health - A 4 week controlled clinical and microbiologic study - Sangeeta Dhir; Viveka Kumar (Wolters Kluwer Medknow Publications, 2018)
Aims: The aim of this study was to compare the efficacy of a powered toothbrush and manual toothbrush on the periodontal and microbial parameters. Settings and Design: This was a 4-week investigator-blinded, single-center, parallel group study. Subjects and Methods: A total of 120 participants were selected and assigned to one of the two toothbrush groups: study group (power toothbrush - Oral-B® CrissCross®) and control group (Oral-B® manual toothbrush). At baseline, gingival status, plaque, and bleeding on probing levels were recorded for the plaque index, gingival index, and bleeding index, respectively. Evaluation of the intraoral soft tissue for safety and clinical parameters was done for plaque, gingival status, and bleeding scores prior to the start of the study (i.e. baseline) and on the 28th day of the study. Statistical Analysis: Two-tailed statistical analyses were performed with a significance level set at P ≤ 0.05 and calculated using SPSS software. Changes in the clinical parameters (plaque index, gingival index, and bleeding index) were calculated using paired t-test. Comparisons between the powered and manual toothbrushes were performed using unpaired t-test. Analysis of categorized data (questionnaire) was done by Fisher's exact test. Results: Clinical parameters were recorded at baseline and on the 28th day. Reduction in plaque, gingival, and bleeding indexes for powered toothbrush was 89%, 85%, and 93% and for manual toothbrush it was 68%, 75%, 72% respectively. A significant reduction was observed in the plaque scores before and after brushing with both the manual and electric brushes. There was no clinically significant soft-tissue abrasion noticed in either of the groups. Preference analysis showed an increased preference for the electric toothbrush over the manual toothbrush. Conclusions: This study concluded that the oscillating-rotating technology as incorporated in the electric toothbrush had statistically significant results over the manual toothbrush and was found to be a safe and effective toothbrush for long-term use.